Analysis of interleukin-1β-modulated mRNA gene transcription in human gingival keratinocytes by epithelia-specific cDNA microarrays - Steinberg, Thorsten; Dannewitz, Bettina; Tomakidi, Pascal; Hoheisel, Jörg D.; Wörtche, Eva; Kohl, Annette; Nees, M. (Journal of periodontal research, 2006)
Proinflammatory cytokines such as interleukin-1β are known to be synthesized in oral gingivitis and periodontitis and lead to the activation of the transcription factor nuclear factor-κB (NF-κB). Although numerous effects of interleukin-1β on mesenchymal cells are known, e.g. up-regulation of intercellular adhesion moelcule-1 in endothelial cells, little is known of the effects of interleukin-1β on oral keratinocytes. The purpose of the present study was to seek interleukin-1β-mediated alterations in mRNA gene transcription and a putative activation of NF-κB in oral gingival keratinocytes.